Analysis of Factors Affecting the Percentage Increase in Company Profit - Ade Erma; Aris Munandar (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2021)
This study aims to analyze the factors that affect the increase in the company's profit PT. Delta Makmur Tbk. This research method uses multiple linear regression and is processed using the SPSS version 16 application. The results of this study indicate that the Current Ratio has no effect and no significant effect on the percentage increase in profit at PT. Delta Dunia Makmur Tbk. Debt to Asset Ratio has no effect and no significant effect on the percentage increase in profit at PT. Delta Dunia Makmur Tbk. Total Asset Turnover There is no effect and no significant effect on the percentage increase in profit at PT. Delta Dunia Makmur Tbk. Net Profit Margin has a significant effect on the percentage increase in profit at PT Delta Dunia Makmur Tbk.